1989 Biennial Exhibition - Armstrong, Richard; Hanhardt, John G.; Marshall, Richard; Phillips, Lisa; W.W. Norton & Company, New York (New York : Whitney Museum of American Art, 1989)
Aaron, Jane ; Antin, Eleanor ; Arvanites, John ; Baechler, Donald ; Bernard, Cindy ; Bickerton, Ashley ; Bleckner, Ross ; Breder, Hans ; Burden, Chris ; Byron, Michael ; Cemin, Saint Clair ; Child, Abigail ; Choy, Chris ; Diamond, Martha ; Donohue, Geralyn ; Dorsky, Nathaniel ; Eisenberg, Daniel ; Ericson, Kate ; Feingold, Ken ; Friedrich, Su ; Gober, Robert ; Gornik, April ; Gottheim, Larry ; Hamada, Sachiko ; Hammer, Barbara ; Heilmann, Mary ; Hill, Gary ; Innerst, Mark ; De Jong, Constance ; Jost, Jon ; Kelley, Mike ; Klosky, Linda ; Koons, Jeff ; Larner, Liz ; Larsen, Ernest ; Levine, Erik ; Levine, Sherrie ; Lord, Chip ; MacDonald, Chris ; Marden, Brice ; Masayesva, Victor Jr. ; McCollum, Allan ; Millner, Sherry ; Moore, Sandy ; Mullican, Matt ; Nelson, Joan ; Noren, Andrew ; Oropallo, Deborah ; Oursler, Tony ; Paik, Nam June ; Perlman, Hirsch ; Puryear, Martin ; Ray, Charles ; Reed, David ; Rosler, Martha ; Scher, Julia ; Shapiro, Joel ; Simon, Jason ; Sinkler, Scott ; Smith, Cary ; Smith, Ray ; Spence, Andrew ; Tajima, Renee ; Tajiri, Rea ; Thornton, Leslie Tillotson ; Torres, Francesc ; Vasulka, Steina ; Vasulka, Woody ; Wallace, Joan ; Wallin, Michael ; Webster, Meg ; Wegman, William ; Wool, Christopher ; Wudl, Tom ; Zalopany, Michele ; Ziegler, Mel
biog., tent., bibliog. per kunstenaar
Engels
Biennial Exhibition 1989, Whitney Museum of American Art, New York, Fourth floor, Lobby Gallery, and Lower Gallery, April 26 - July 16 ; Second floor and Second floor Film/Video Gallery, April 18 - July 9, 19891989-04-18. 1989-07-16
boek